Latissimus Dorsi (LD) Flap with Immediate Fat Transfer versus Implant-Based LD Flap for Breast Reconstruction: A Retrospective Comparison of 402 Patients - Miettinen, Tiia (My University, 2026)
Breast reconstruction following mastectomy can be performed using either implant-based or autologous techniques. Although abdominal free flaps are widely considered the gold standard for autologous reconstruction, not all patients are suitable candidates due to comorbidities, smoking status, or personal preferences. In such cases, the latissimus dorsi (LD) flap remains an important reconstructive option. Traditionally, LD reconstruction has often required an implant to achieve adequate breast volume. However, immediate fat transfer to the LD flap (fat-augmented latissimus dorsi, FALD) has emerged as an alternative that allows volume enhancement without implants. This retrospective study compared outcomes of FALD and implant-assisted LD reconstruction in 402 patients treated at Turku University Hospital between 2009 and 2024. Demographic data, operative details, and postoperative complications were analyzed. Of the patients, 130 underwent FALD reconstruction and 272 implant-assisted LD recontruction. Overall complication rates were similar between the groups, and no statistically significant differences were observed in major or wound-related complications. Operative time was identified as an independent predictor of postoperative complications. Both techniques demonstrated comparable safety profiles. FALD offers a fully autologous alternative that avoids implant-related complications, whereas implant-assisted LD reconstruction may provide greater immediate breast volume. Further prospective studies are needed to optimize patient selection and evaluate long-term outcomes.
Keywords: Rintarekonstruktio; LD-rekonstruktio; implantti; postoperatiivinen komplikaatio